ChemInform Abstract: Efficient Access to 2, 3‐Dihydroquinazolin‐4(1H)‐ones by Environmentally Benign L‐Proline Nitrate as Recyclable Catalyst. Issue 13 (March 2016) - Bahekar, Sandeep P.; Dahake, Nityanand D.; Sarode, Prashant B.; Chandak, Hemant S.
Abstract: L‐Proline nitrate is used as a green catalyst for a one‐pot cyclocondensation of anthranilamide and aldehydes under mild conditions.